The effect of selected marketing activities and promotions on the consumers buying behavior - Alhalalmeh, Mohammad; Alkhawaldah, Reyad Abdallah; Mohammad, Anber; Al-Quran, Ali; Hijjawi, Ghufran; Al-Hawary, Sulieman (Business: Theory and Practice, 2022)
The core purpose of this study is to determine the impact of electronics marketing (word of mouth), perceived value, and social networking on customer buying behaviour through customer trust in the context of cosmetic industry of Jordan. To accomplish the main research objective, the study has followed SEM technique for analysing collected data. For data collection, the use of survey questionnaire has been made, in which data was collected from total 223 respondents. The results of this study confirm the significant impact of perceived value on customer trust and customer buying behaviour, whereas electronic marketing (word of mouth) was found to have insignificant impact on both customers buying behaviour and customer trust. Findings also revealed the significant impact of social networking networks on customer buying behaviour. However, its impact on customer trust was insignificant. With respect to mediating effect, customer trust significantly mediates the association between perceived value and customer buying behaviour.